Can two-player games increase motivation in rehabilitation robotics? - Novak, Domen; Nagle, Aniket; Riener, Robert (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
Rehabilitation robots have the potential to greatly improve motor rehabilitation. However, the patient must be properly motivated to actively participate in therapy. Several strategies have been suggested to improve patient motivation, but one element has not yet been explored: playing with other people. We designed a two-player rehabilitation game played by two people using two ARMin III robots. We tested three game modes: single-player (competing against a computer), competitive (competing against a human), and cooperative (cooperating with a human against a computer). All modes were played by 24 healthy subjects who filled out questionnaires about their personality and in-game motivation. Almost all subjects preferred playing the two-player game modes to the single-player one, as they enjoyed being able to talk and interact with another person. However, there were two distinct player groups. One group liked the competitive mode but not the cooperative mode while the other liked the cooperative but not the competitive mode. Subjects who liked the competitive mode also put more effort into it. Finally, subjects' personalities partially predicted what mode they would like. This emphasizes that two-player rehabilitation games have advantages over single-player ones, but that the right game needs to be chosen for each subject. An extended patient study is planned for the near future.